Analisis Service Quality Menggunakan Metode Importance Performance Analysis (Ipa) Pada Pt Clandestin Kreasi Mandiri Tahun 2023 - Tarigan, Febby Oktalina BR; Widaningsih, Sri (eProceedings of Applied Science, 2023)
More and more brands and companies in Indonesia are improving service quality to meet the expectations of company customers, maintain customer satisfaction, and gain loyal customers as an important asset for business continuity. Organizing a successful event largely depends on the quality of services provided by the event planner. This research aims to analyze the factors that influence service quality in event planning and its impact on client satisfaction. The research results show that service quality in event planning has a significant role in creating a positive experience for clients. The purpose of this research is to determine the performance expectations and level of satisfaction with PT Clandestin Kreasi Mandiri by examining 100 respondents. The method used is descriptive research analysis with quantitative data types. The discussion analysis used is Importance Performance Analysis (IPA). This research uses the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods with 5 dimensions (service quality), namely tangible, empathy, reliability, responsiveness and assurance. The results of the descriptive analysis of Importance and performance based on the Servequal dimension at PT Clandestin Kreasi Mandiri are 78.50% which is on the line between 62.50% - 81.25%, which means they are both high.Kata kunci: Service Quality, Metode Importance Performance Analysis, Customer statisfactin index (CSI)